2014
DOI: 10.1007/s00264-014-2391-1
|View full text |Cite
|
Sign up to set email alerts
|

Biologic augmentation of rotator cuff repair with mesenchymal stem cells during arthroscopy improves healing and prevents further tears: a case-controlled study

Abstract: This study showed that significant improvement in healing outcomes could be achieved by the use of BMC containing MSC as an adjunct therapy in standard of care rotator cuff repair. Furthermore, our study showed a substantial improvement in the level of tendon integrity present at the ten-year milestone between the MSC-treated group and the control patients. These results support the use of bone marrow-derived MSC augmentation in rotator cuff repair, especially due to the enhanced rate of healing and the reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
339
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(346 citation statements)
references
References 31 publications
6
339
1
Order By: Relevance
“…The usage of autologous cells at the point-of-care is an appealing alternative, with less regulatory requirements and a decreased risk of cell contamination or rejection. A growing amount of data has suggested strong correlations in clinical outcomes with non-union fracture, degenerative disc disease, rotator cuff tear, avascular necrosis, and other orthopedic injuries, based on the concentration of MSCs present in bone marrow at physiological levels, or concentrated up to 10× [17][18][19]. The effects of non-cultured MSC concentration on bone formation when combined with HA granular particles are presently unreported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The usage of autologous cells at the point-of-care is an appealing alternative, with less regulatory requirements and a decreased risk of cell contamination or rejection. A growing amount of data has suggested strong correlations in clinical outcomes with non-union fracture, degenerative disc disease, rotator cuff tear, avascular necrosis, and other orthopedic injuries, based on the concentration of MSCs present in bone marrow at physiological levels, or concentrated up to 10× [17][18][19]. The effects of non-cultured MSC concentration on bone formation when combined with HA granular particles are presently unreported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…A followup study showed that transducing allogeneic, marrow-derived MSCs with scleraxis improved the amount of fibrocartilage present at the tendon-bone interface at the 4-week time point [21]. Hernigou et al presented a case series of 45 human patients who underwent arthroscopic rotator cuff surgery augmented with a heterogenous population of stem and progenitor cells taken from intraoperative iliac crest marrow aspirates [24]. The authors reported evidence of enhanced healing through ultrasound, MRI, and functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of the biologic augmentation of the rotator cuff repair using iliac BM-MSCs has been evaluated in 45 patients by Hernigou et al [8]. A significant improvement in healing outcomes has been achieved, supporting the use of MSC augmentation and a reduced number of re-tears observed in MSC treated patients.…”
mentioning
confidence: 95%